2020
DOI: 10.1109/access.2020.2969849
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Cluster Validity Indices for Online Learning of Hard Partitions: Extensions and Comparative Study

Abstract: Validation is one of the most important aspects of clustering, but most approaches have been batch methods. Recently, interest has grown in providing incremental alternatives. This paper extends the incremental cluster validity index (iCVI) family to include incremental versions of Calinski-Harabasz (iCH), I index and Pakhira-Bandyopadhyay-Maulik (iI and iPBM), Silhouette (iSIL), Negentropy Increment (iNI), Representative Cross Information Potential (irCIP) and Representative Cross Entropy (irH), and Conn Inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 87 publications
0
23
0
Order By: Relevance
“…[9] and [3] introduced and evaluated the incremental Davies-Bouldin (iDB) and Xie-Beni (iXB) indices for their applicability to accurately and poorly partitioned data sets while [10] and [11] investigated the behavior of iDB in cases in which the clustering methods accurately detected structures present in the data. [4] extended this family of iCVIs to include six additional versions. In that work, it was found that certain iCVIs are more effective at identifying certain partition conditions.…”
Section: Background and Related Work A Clusteringmentioning
confidence: 99%
See 2 more Smart Citations
“…[9] and [3] introduced and evaluated the incremental Davies-Bouldin (iDB) and Xie-Beni (iXB) indices for their applicability to accurately and poorly partitioned data sets while [10] and [11] investigated the behavior of iDB in cases in which the clustering methods accurately detected structures present in the data. [4] extended this family of iCVIs to include six additional versions. In that work, it was found that certain iCVIs are more effective at identifying certain partition conditions.…”
Section: Background and Related Work A Clusteringmentioning
confidence: 99%
“…Indeed, methods have been proposed which focus solely on the proper selection of an CVI for optimal results on a particular data set [13]. However, an extension of [4] found that a single iCVI can serve as a vigilance mechanism for Fuzzy ART [14] as well as for TopoARTMAP [15]. The former study investigated iCH, iWB, iXB, iDB, incremental Pakhira-Bandyopadhyay-Maulik (iPBM), and incremental Negentropy Increment (iNI).…”
Section: Background and Related Work A Clusteringmentioning
confidence: 99%
See 1 more Smart Citation
“…CVIs are useful as one of the only methods of determining the performance of a clustering algorithm in the absence of explicit labels (Arbelaitz et al, 2013). Furthermore, ICVIs can measure the performance of clustering algorithms as they are running in a computationally tractable manner, which is incredibly useful in a variety of streaming clustering applications (Brito Da Silva et al, 2020).…”
Section: Statement Of Needmentioning
confidence: 99%
“…In fact, it is often the trendlines of these values that provide the most information about the clustering process rather than the values themselves. incremental variants that are proven to be mathematically equivalent to their batch counterparts (Brito Da Silva et al, 2020). These incremental CVIs (ICVIs) mitigate the computational overhead of computing these metrics online, such as in a streaming clustering scenarios.…”
Section: Cluster Validity Indicesmentioning
confidence: 99%